2018
DOI: 10.1002/cssc.201800874
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Titanium Dioxide Nanomaterials for Photocatalytic Applications

Abstract: Environmental and energy problems have drawn much attention owing to rapid population growth and accelerated economic development. For instance, photocatalysis, "a green technology", plays an important role in solar-energy conversion owing to its potential to solve energy and environmental problems. Recently, many efforts have been devoted to improving visible-light photocatalytic activity by using titanium dioxide as a photocatalyst as a result of its wide range of applications in the energy and environment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(118 citation statements)
references
References 337 publications
(567 reference statements)
1
109
0
2
Order By: Relevance
“…TiO 2 is acclaimed as a UV‐light photocatalytic. To enhance TiO 2 performance in visible light, many approaches investigate the doping of TiO 2 with metal transitions . While doping, a disordered structure could appear in TiO 2 , limiting the efficiency of this approach.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 is acclaimed as a UV‐light photocatalytic. To enhance TiO 2 performance in visible light, many approaches investigate the doping of TiO 2 with metal transitions . While doping, a disordered structure could appear in TiO 2 , limiting the efficiency of this approach.…”
Section: Applicationsmentioning
confidence: 99%
“…To enhance TiO 2 performance in visible light, many approaches investigate the doping of TiO 2 with metal transitions. [111][112][113] While doping, a disordered structure could appear in TiO 2 , limiting the efficiency of this approach. Perovskite structure ABO 3 has been investigated because A site is shared by two cations without causing a disordered lattice.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…Several studies showed that TiO 2 and TiO 2 ‐based materials have great application potential and inestimable value as photocatalysts . However, they still suffer from inferior solar light harvesting, low quantum efficiency (QE), low solar energy utilization, and rapid recombination of electron‐hole pairs …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Al arge number of poisonous and harmful compounds are released into the environment because of lack of effective methods fort reatingt hese pollutants. [4][5][6] Photocatalysis is ap otentialt echnology for solving environmental and energy problemsi ncluding degradation of pollutants, H 2 productionvia water splitting and dye-sensitized solar cell, and selective oxidation reactions. [7][8][9][10][11][12] However,t his strategy remains inefficient due to the challenge: difficultiesi ne nergy band configuration limit sunlight utilization to mainly within the ultraviolet and visible light region, resulting in near-infrared light (NIR, 54 %o fs olar radiation at the Earth's surface) unable to be harvested.…”
Section: Introductionmentioning
confidence: 99%